Effectiveness of private tutoring during secondary schooling in Germany: Do the duration of private tutoring and tutor qualification affect school achievement? - Ömeroğulları, Melike; Guill, Karin; Köller, Olaf (Learning and Instruction, 2020)
Private tutoring is considered an effective measure to improve academic achievement. However, previous studies have come to different conclusions regarding its effectiveness. In this study, we conducted secondary analyses using data of two longitudinal studies (approx. 8000 secondary school students) and investigated the effects of private tutoring duration and different levels of tutors' formal qualifications on subject-specific grades and test scores in 4 school subjects. OLS-regression analyses showed neither a systematic positive effect of a longer duration of tutoring nor of higher qualified tutors when prior knowledge, motivational and sociodemographic variables were controlled for. However, we found significant positive interaction effects between tutors' qualifications and students’ prior knowledge in German tutoring. Overall, we find only weak evidence that private tutoring is effective but show that students may benefit from private tutoring under certain conditions.
Keywords: Effectiveness; Private tutoring; Secondary school; Tutoring duration; Tutors' formal qualifications